2021
DOI: 10.1038/s41420-021-00630-w
|View full text |Cite
|
Sign up to set email alerts
|

Loss of mpv17 affected early embryonic development via mitochondria dysfunction in zebrafish

Abstract: MVP17 encodes a mitochondrial inner-membrane protein, and mutation of human MVP17 can cause mitochondria DNA depletion syndrome (MDDS). However, the underlying function of mpv17 is still elusive. Here, we developed a new mutant with mpv17 knockout by using the CRISPR/Cas9 system. The mpv17−/− zebrafish showed developmental defects in muscles, liver, and energy supply. The mpv17−/− larvae hardly survived beyond a month, and they showed abnormal growth during the development stage. Abnormal swimming ability was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…In this study, we demonstrated that CG11077 , an MPV17/PMP22 family gene, is a Drosophila ortholog of mammalian Mpv17 and named it dMpv17 . Human Mpv17 is known as a causal gene of MPV17 -related hepatocerebral MDDS and CMT 4 , 6 , 8 , and models of these diseases have been developed in several organisms such as the mouse and zebrafish 10 , 17 . However, in spite of the fact that most patients show neurological symptoms, neurological defects have not been investigated in these model organisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we demonstrated that CG11077 , an MPV17/PMP22 family gene, is a Drosophila ortholog of mammalian Mpv17 and named it dMpv17 . Human Mpv17 is known as a causal gene of MPV17 -related hepatocerebral MDDS and CMT 4 , 6 , 8 , and models of these diseases have been developed in several organisms such as the mouse and zebrafish 10 , 17 . However, in spite of the fact that most patients show neurological symptoms, neurological defects have not been investigated in these model organisms.…”
Section: Discussionmentioning
confidence: 99%
“…MPV17 deficiency in mice leads to a reduced deoxynucleotide pool resulting in mtDNA depletion in the liver, but not in the kidney or brain 2 . In zebrafish, diverse phenotypes have been reported in two mpv17 mutants (roy orbison (roy) and transparent (tra)), and Mpv17 KO zebrafish generated by the CRISPR/Cas9 system [13][14][15][16][17] . While roy and tra mutants show only transparent phenotypes with a loss or strong reduction of iridophores and melanophores, Mpv17 KO zebrafish show reduced longevity and defects in muscle, liver, and energy supply during development in addition to a strong reduction of iridophores and melanophores [13][14][15][16][17] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 C ). There are several studied mutations of mpv17 all with loss of irridophores ( Bian et al, 2021 ). Here, we use the naturally occurring 19-base-pair intronic deletion of the roy orbison mutant ( D’Agati et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…SYM1, the yeast ortholog of MPV17, exhibits strong evolutionary conservation as its depletion can be complemented by human MPV17 expression which can rescue the impaired OXPHOS activity and growth defect under non-fermentable condition (Dallabona et al, 2010). SYM1 depletion leads to mitochondrial ultrastructure defects (Dallabona et al, 2010), as also observed in glomeruli cells of MPV17 -/--related kidney disease mouse model (Luna-Sanchez et al, 2020) and in mpv17 -/zebrafish larvae muscle (Bian et al, 2021). The maintenance of the mitochondrial ultrastructure is mainly achieved by the MItochondrial contact site and Cristae Organizing System (MICOS) complex, which is part of the Mitochondrial Intermembrane space Bridging (MIB) supercomplex.…”
Section: Introductionmentioning
confidence: 94%